Restorative Justice in Settling Minor Criminal Disputes in Ponorogo, East Java: An Islamic Law Perspective - Munawaroh, Hifdhotul (Mazahib, 2019)
This article aims at examining the viability of a village court as an alternative settlement of minor criminal disputes in the district of Mlarak, Ponorogo, East Java. Among the cases resolved through restorative justice are petty theft, juvenile delinquencies, crimes against women and children, and public order disruption. The village court has used mediation among the disputants in the search of a consensus without harming each party. The consensus achieved signifies the return of balance in the community which has been damaged by the offenses. This makes dispute resolution through mediation and customary justice in line with the concept of Restorative Justice. However, there are obstacles in the resolution of cases through mediation. This includes: first, there are no regulations governing village justice procedures so that the mediation and village justice procedures differ from one village to another. Second, the determination of sanctions for minor criminal offenses is perceived to have not deterred some of the perpetrators. This is evidenced by the repetition of criminal acts committed by the perpetrators which, thus, has created public unrest. Third, the level of understanding of community leaders towards the law is still lacking. This has resulted in discrepancies in settling the disputes. From the Islamic law perspective, the settlement of a dispute by means of the village justice is in accordance with the Sharia. It constitutes the implementation of al-shulh system and taâ€˜zÄ«r concept in the provision of punishment for the perpetratorsÂ Keyword: Restorative Justice, al-Sulh, Alternative Dispute Resolution (ADR), Minor Criminal Disputes